Health Security Intelligence: engaging across disciplines and sectors. Issue 4 (6th June 2020) - Lentzos, Filippa; Goodman, Michael S.; Wilson, James M.
ABSTRACT: This article introduces the Special Issue on Global Health Security. It provides an overview of the health security threat spectrum, tracing how perceptions of biological and health security threats have evolved in broad terms over the last century from deliberately introduced disease outbreaks to also incorporate natural disease outbreaks, unintended consequences of research, laboratory accidents, lack of awareness, negligence, and convergence of emerging technologies. This spectrum of threats has led to an expansion of the stakeholders and tools involved in intelligence gathering and threat assessments. The article argues that to strengthen global health security and health intelligence, the traditional state-based intelligence community must actively engage with non-security stakeholders and incorporate space for new sources of intelligence. The aim of the Special Issue is to contribute to the larger effort of developing a multidisciplinary, empirically informed and policy-relevant approach to intelligence-academia engagement in global health security that serves both the intelligence community and scholars from a broad range of disciplines.